2018
DOI: 10.1038/s41386-018-0301-8
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter inhibition and 5-HT2C receptor activation drive loss of cocaine-induced locomotor activation in DAT Val559 mice

Abstract: Dopamine (DA) signaling dysfunction is believed to contribute to multiple neuropsychiatric disorders including attention-deficit/hyperactivity disorder (ADHD). The rare DA transporter (DAT) coding substitution Ala559Val found in subjects with ADHD, bipolar disorder and autism, promotes anomalous DA efflux in vitro and, in DAT Val559 mice, leads to increased reactivity to imminent handling, waiting impulsivity, and enhanced motivation for reward. Here, we report that, in contrast to amphetamine and methylphenid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…Attention-deficit/hyperactivity disorder (ADHD) is a neuropsychiatric disorder that occurs most frequently in school-age children and is characterized as inattention with or without excessive impulsivity and hyperactivity (Abramov et al, 2019). Previous studies have reported that ADHD pathogenesis may be associated with dysregulation of neurotransmitters such as dopamine, serotonin (5-hydroxytryptamine, 5-HT), and norepinephrine (Magula et al, 2019;Stewart et al, 2019;Suzuki et al, 2019). Others have shown that the incidence of ADHD may have a certain degree of heritability, and genes related to dopamine, norepinephrine, and 5-HT transmission have been found to be abnormally expressed in children with ADHD (Banerjee and Nandagopal, 2015;Karmakar et al, 2017;Kim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Attention-deficit/hyperactivity disorder (ADHD) is a neuropsychiatric disorder that occurs most frequently in school-age children and is characterized as inattention with or without excessive impulsivity and hyperactivity (Abramov et al, 2019). Previous studies have reported that ADHD pathogenesis may be associated with dysregulation of neurotransmitters such as dopamine, serotonin (5-hydroxytryptamine, 5-HT), and norepinephrine (Magula et al, 2019;Stewart et al, 2019;Suzuki et al, 2019). Others have shown that the incidence of ADHD may have a certain degree of heritability, and genes related to dopamine, norepinephrine, and 5-HT transmission have been found to be abnormally expressed in children with ADHD (Banerjee and Nandagopal, 2015;Karmakar et al, 2017;Kim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism of 5-HT in the brain directly affects or is related to human mental activity. A large number of studies have shown that 5-HT metabolic abnormalities play important role in the pathophysiological mechanism of TS [ 26 ], anxiety disorders [ 27 ], ADHD [ 28 ], OCD [ 29 , 30 ] and other mental behavior disorders. Fluoxetine, a selective serotonin reuptake inhibitor, as the first-line psychological treatment to counter TS and comorbid anxiety also supports the association of 5-HT dysfunction with TS and comorbid anxiety [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it reflects the absence of common risk variants. Several rare coding DAT variants with functional deficits both in vitro and in vivo have been identified in patients with psychiatric disorders (Bowton et al, 2014;Campbell et al, 2019;Cartier et al, 2015;Davis et al, 2018;DiCarlo et al, 2019;Gowrishankar et al, 2018;Grunhage et al, 2000;Hamilton et al, 2013;Hansen et al, 2014;Herborg et al, 2018;Mazei-Robison et al, 2005;Sakrikar et al, 2012;Stewart et al, 2019;Wu et al, 2015) but the causal link between these putative risk alleles and disease is still elusive as the family trees and cohort sizes have been too small for meaningful linkage or association analysis. We have, to the best or our knowledge, carried out the first association analysis of a coding DAT variant using large-scale exome data, and demonstrate a nominally significant association to bipolar disease.…”
Section: Discussionmentioning
confidence: 99%